Phylogenetic analysis of pathogenic isolates of the botryosphaeriaceae family in cacao (Theobroma cacao L.) in the Los Ríos area - Jiménez, Wendy (2022)
Phytosanitary problems caused by vascular fungi affecting CCN-51 cocoa plantations have become very important in recent decades, due to the damage they cause. Species of the Botryosphaeriaceae family are associated with cankers and drying of buds, downward death, fruit rot and neck rot, symptoms that have been observed in different areas and that reduce plant production. In order to characterize and identify pathogenic isolates of this fungus at the molecular level, five symptomatic trees were sampled from farms located in the cantons of: Buena Fe, Mocache, Quevedo, Quinsaloma and Valencia of the province of Los Rios, obtaining 15 isolates from which DNA was extracted and sequences from the ITS (Internal transcribed spacer) and EF1-a (Elongation factor of alpha) regions were used. Sequence sizes were verified by electrophoresis and putative identities of 3 species were established using the Basic local aligment tool (BLAST). Phylogenetic trees constructed using maximum likelihood and nearest neighbor algorithms, with isolates in five cantons, confirmed the presence of Lasiodiplodia theobromae in Quevedo, Diplodia seriata in Quinsaloma and Botryosphaeria dothidea in Valencia, Mocache and Buena Fe, highlighting a polytomy among the latter.